Discrimination and ethnic group identity as explanations of British ethnic minority political behaviour - Martin, N (2015)
This thesis looks at the role of discrimination and ethnic group identity as explanations of political behaviour of ethnic minorities in Britain. Chapter 2 examines vote choice and partisanship, arguing that a group utility heuristic explains the high level of support for the Labour party among ethnic minorities. I provide individual-level evidence of this heuristic by showing that ethnic minority voters support the Labour party to the extent that they are (i) conscious of the experiences of their ethnic group members with regards to discrimination, and (ii) believe that the Labour party is the best political party to represent their interests. These two attitudes mediate the effects of group-level inequalities. Chapter 3 asks whether Muslims are alienated from mainstream politics by Islamophobia and British military intervention in Muslim countries. I find that perceptions of Islamophobia are linked with greater political alienation, to a greater likelihood of non-electoral participation, but also to a lesser likelihood of voting. Likewise, disapproval of the war in Afghanistan is associated with greater political alienation and a greater likelihood of some types of non-electoral participation. I also provide strong evidence that Muslims in Britain experience more religious discrimination than adherents of other minority religions. Chapter 4 considers the interaction between the extreme right and ethnic minority political attitudes and behaviour. I find evidence that the extreme right British National Party (BNP) increases voting for the Labour party, at the expense of minor parties and abstention. Surprisingly, the BNP effect also benefits the other main parties. Although they do not benefit in increased vote share, Liberal Democrat and Conservative party and leader evaluations are more positive where the BNP stood and performed better in 2010, which I suggest is due to the electoral contrast provided by the BNP. Chapter 5 looks at the mobilisation effect of ethnic minority candidates on ethnic minority voters. I find a positive mobilisation effect of Pakistani and Muslim Labour candidates on Pakistani and Muslim voters, conditional on someone trying to convince the respondent how to vote. I also find a demobilisation effect of Labour Muslim candidates on Sikh voters.